2013
DOI: 10.1037/a0032344
|View full text |Cite
|
Sign up to set email alerts
|

Family support, self-esteem, and perceived racial discrimination among Asian American male college students.

Abstract: This study was conducted to examine under what situation (i.e., when individuals used more or less family support) and for whom (i.e., those with high or low self-esteem) perceived racial discrimination would or would not have a significant positive association with psychological distress. A total of 95 Asian American male college students completed an online survey. A hierarchical regression analysis indicated a significant 3-way interaction of family support, self-esteem, and perceived racial discrimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 47 publications
4
39
0
1
Order By: Relevance
“…More specifically, we found that MEAAs who have low to moderate (but not high) levels of family connectedness are vulnerable to psychological distress associated with ethnic discrimination. This finding is consistent with research with other ethnic minority populations showing that high family connectedness buffered the racial or ethnic discriminationnegative mental health outcomes link (e.g., Chae et al, 2012;Stuart & Jose, 2014;Tummala-Narra et al, 2012;Wei et al, 2010Wei et al, , 2013Umaña-Taylor et al, 2011. However, we also found that higher levels of family connectedness were related to more psychological distress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More specifically, we found that MEAAs who have low to moderate (but not high) levels of family connectedness are vulnerable to psychological distress associated with ethnic discrimination. This finding is consistent with research with other ethnic minority populations showing that high family connectedness buffered the racial or ethnic discriminationnegative mental health outcomes link (e.g., Chae et al, 2012;Stuart & Jose, 2014;Tummala-Narra et al, 2012;Wei et al, 2010Wei et al, , 2013Umaña-Taylor et al, 2011. However, we also found that higher levels of family connectedness were related to more psychological distress.…”
Section: Discussionsupporting
confidence: 91%
“…Family connectedness is a likely source of support and strength that could minimize depressed and anxious symptoms. Indeed, the evidence for family connectedness as a protective factor against negative psychological outcomes has been supported in the literature with other ethnic minority groups, most notably Asian Americans (Chae, Lee, Lincoln, & Ihara, ; Tummala‐Narra, Alegria, & Chen, ; Wei, Yeh, Chao, Carrera, & Su, ), Latino/as (Umaña‐Taylor, Updegraff, & Gonzales‐Backen, ), and Maori in New Zealand (Stuart & Jose, ). For example, Tummala‐Narra et al.…”
Section: Moderators Of the Ethnic Discrimination–distress Linksmentioning
confidence: 95%
“…This area of research is often situated within the field of psychology (Alvarez & Helms, 2001; Hsin & Xie, 2014; M. Lee & Thai, 2015; Maddox, 2004; Thompson et al, 2016; Wei et al, 2013; Xu et al, 2014). Although many of these studies examine conditions that affect or result in differing levels of self-confidence and self-esteem, none of them focus on how it connects or speaks to Asian American college choice.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Berdasarkan definisi tersebut peneliti hendak melihat seberapa besar mahasiswa kebidanan menilai dirinya berharga atau layak untuk menjadi bidan di tengah isu-isu negatif dalam dunia kebidanan. Kecenderungan munculnya self-esteem pada individu dapat dipengaruhi oleh beberapa faktor yaitu, keluarga (Wei, Yeh, Chao, Carrera, & Su, 2013;Orth, Maes, & Schmitt, 2015), status sosioekonomi (Chen, Niu, Zhang, Fan, Tian, & Zhou, 2016), Pengalaman keberhasilan dan kegagalan sebelumnya (Harter, 1999dalam Heinonen, Raikkonen, & Keltikangas-Jarvinen, 2005, budaya (Tsai, Ying, & Lee, 2001), dan religiusitas (Watson et al, 2002;Maltby, Lewis, & Day, 1999). Pada penelitian ini, pengukuran variabel self-esteem menggunakan Rosenberg's Self-esteem Scale (RSE) yang dikembangkan oleh Rosenberg pada tahun 1965 (Guindon, 2010).…”
Section: Self-esteemunclassified